2018
DOI: 10.15293/1813-4718.1805.10
|View full text |Cite
|
Sign up to set email alerts
|

The Specificity of the Life Trajectory and Indicators of Subjective Well-Being of Adults with Hearing Impairment

Abstract: Permission to submit a PhD thesis in alternative format 19 6. Concept of mental well-being 7. Conclusion Chapter Three: Methodology 1. Overview mental health outcomes 4.2. Social, familial and environmental factors in childhood relating to mental health difficulties outcomes in adulthood 4.3. Mental health difficulties in childhood and the outcomes in adulthood (other than mental health) 4.4. The importance of services for young people with mental health difficulties 4.5. Conclusions of the findings from heari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Summarizing the work of researchers in this area the following structural components of this formation can be distinguished [1,14,16,17] The experimental study was carried out on the basis of an educational organization that has been implementing inclusive educational practice for more than 15 years. The study involved 50 parents of children with disabilities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarizing the work of researchers in this area the following structural components of this formation can be distinguished [1,14,16,17] The experimental study was carried out on the basis of an educational organization that has been implementing inclusive educational practice for more than 15 years. The study involved 50 parents of children with disabilities.…”
Section: Methodsmentioning
confidence: 99%
“…Yagovkina and other researchers have shown that the involvement (complicity) of parents of different categories of students, based on the attitude of parents to an inclusive educational environment, on their satisfaction with relationships with other subjects of the educational process, is ensured by the willingness of parents to teach children together in an inclusive educational environment. This allows the inclusive educational environment to be safe and to solve its primary task -socialization and social integration of all students [1,14,16,17].…”
Section: Introductionmentioning
confidence: 99%